Specificity of time- and dose-dependent morphological endpoints in the fish embryo acute toxicity (FET) test for substances with diverse modes of action: the search for a “fingerprint” - Hellfeld, Rebecca von; Pannetier, Pauline; Braunbeck, Thomas (Environmental science and pollution research, 2022)
The fish embryo acute toxicity (FET) test with the zebrafish (Danio rerio) embryo according to OECD TG 236 was originally developed as an alternative test method for acute fish toxicity testing according to, e.g., OECD TG 203. Given the versatility of the protocol, however, the FET test has found application beyond acute toxicity testing as a common tool in environmental hazard and risk assessment. Whereas the standard OECD guideline is restricted to four core endpoints (coagulation as well as lack of somite formation, heartbeat, and tail detachment) for simple, rapid assessment of acute toxicity, further endpoints can easily be integrated into the FET test protocol. This has led to the hypothesis that an extended FET test might allow for the identification of different classes of toxicants via a “fingerprint” of morphological observations. To test this hypothesis, the present study investigated a set of 18 compounds with highly diverse modes of action with respect to acute and sublethal endpoints. Especially at higher concentrations, most observations proved toxicant-unspecific. With decreasing concentrations, however, observations declined in number, but gained in specificity. Specific observations may at best be made at test concentrations ≤ EC10. The existence of a “fingerprint” based on morphological observations in the FET is, therefore, highly unlikely in the range of acute toxicity, but cannot be excluded for experiments at sublethal concentrations.